(untitled) - John A Timbrell (London, 1994)
The book contains figures, examples, information that together provide a wide ranging introduction to toxicology, covering the basic principles and processes, such as dose-response relationships, disposition and metabolism, and then developing to address toxic response and biochemical mechanisms of toxicity
Keywords: biochemical toxicology